Synthesis and Neuropharmacological Evaluation of Some Novel Quinoxaline 2, 3-Dione Derivatives - Selvaraj Jubie; Rajamanickam Gayathri; Rajagopal Kalirajan (The Scientific World Journal)
Quinoxaline-2, 3-dione obtained from cyclocondensation reaction of o-phenylene diamine with oxalic acid was reacted with three different ketones and formaldehyde to give the corresponding Mannich bases in satisfactory yield. Their structures were confirmed by using 1H NMR, IR, and mass analysis. In pharmacological evaluation, the synthesized compounds showed its curative effect against ethidium-bromide-induced demyelination in rats. For the purpose, different screening methods such as open field exploratory behavior test, rota rod test, grip strength test, beam walk test, and photo actometer test were performed. Ethidium bromide induction showed muscle weakness; muscle discoordination; loss of locomotor activity, and so forth, the synthesized drugs reversed all the above-mentioned neuromuscular disorders caused by ethidium bromide administration.